Conflict over Women’s Working Times on the Eve of Industrialisation: Spanish Social Reformers’ Surveys at the End of the Nineteenth Century - Borderías, Cristina (The Historical Review/La Revue Historique, 2019)
During the last two decades of the nineteenth century, Spain experienced growing social instability. The worsening working conditions stimulated social conflict and the rise of the labour movement. In this context, the first voices in favour of state intervention in conflicts between capital and labour arose among the reformist intellectual elite. One of the first social policy measures undertaken by the state was the creation, in 1883, of the Comisión de Reformas Sociales (Commission for Social Reforms, CRS) as a consultative and advisory institution of the government on social issues. Under the influence of positivist methods of empirical sociology, the commission’s first initiative was to conduct a survey with the objective of undertaking a detailed diagnosis of the living conditions of the working population. Changing gender relations in the family and labour market, especially the conflicts over the use of women’s time, was one of the central questions in this survey. Thus, its results allow us to analyse both the discourses – by social reformers and other social groups – and the social practices of women at work in different sectors and in different parts of Spain.